Relational spaces in Architecture, Aesthetics and Education : The Italian neo avant-garde architecture and the case of the Reggio Emilia Approach. - Manera, Lorenzo (Scenari, 2021)
This paper explores the relevant connections existing between the concepts developed by the most relevant Italian neo avant-garde Architecture groups, such as Archizoom or Superstudio, and the concept of environment developed by Loris Malaguzzi. Furthermore, the paper explores the role played by the architects Tullio Zini and Andrea Branzi in the development of the aesthetic of the environment evolved in the Reggio Emilia Approach. Finally, the paper discusses the hypothesis that Malaguzzi’s relational pedagogy and Branzi’s idea of relational space were not only in direct dialogue, but also share a common cultural background rooted in the aesthetics of the neo-avant garde.